miRMap: Profiling 14q32 microRNA Expression and DNA Methylation Throughout the Human Vasculature - Goossens, Eveline A. C.; de Vries, Margreet R.; Simons, Karin H.; Putter, Hein; Quax, Paul H. A.; Nossent, A. Yaël (Frontiers in Cardiovascular Medicine, 2019)
Aims: MicroRNAs are regulators of (patho)physiological functions with tissue-specific expression patterns. However, little is known about inter-vascular differences in microRNA expression between blood vessel types or vascular beds. Differences in microRNA expression could influence cardiovascular pathophysiology at specific sites in the vasculature. Therefore, we aimed to map expression profiles of vasoactive 14q32 microRNAs throughout the human vasculature, as well as expression of vasoactive target genes of the 14q32 microRNAs. Furthermore, we aimed to map the DNA methylation status of the 14q32 locus, which has been linked to cardiovascular disease. Methods and Results: We collected 109 samples from different blood vessels, dissected during general surgery. Expression of a representative set of 17 14q32 microRNAs was measured in each sample. All 17 microRNAs showed a unique expression pattern throughout the vasculature. 14q32 microRNA expression was highest in lower limb vessels and lowest in head and neck vessels. All 17 microRNAs were expressed more abundantly in arteries than in veins. Throughout the human vasculature, we observed trends towards an inverse correlation between expression levels of the 14q32 microRNAs and their vasoactive target genes. DNA methylation of the 3 Differentially Methylated Regions (DMRs) along the 14q32 locus did not associate with primary or mature microRNA expression. However, hyper-methylation in venous coronary artery bypass grafts compared to arterial bypass grafts was observed in the Intergenic-DMR and MEG3-DMR. In patients with end-stage peripheral arterial disease we found differential DNA methylation throughout all DMRs in their lower limb veins. These findings were confirmed in a mouse model for vein-graft disease in which we found regulated 14q32 DNA methylation during the active phase of vascular remodelling. In ischemic tissues of a murine hind limb ischemia model we observed an increase in DNA methylation associated with increased ischemia over time. Conclusions: We show that 14q32 microRNAs are abundantly expressed in the human vasculature and that expression differs significantly between different blood vessels. 14q32 DNA methylation also varies throughout the vasculature and is associated with vascular health, independently of microRNA levels. These findings could have important implications for future research and for future site-specific targeting of epigenetics-based therapeutics.